The role of fatty acids in attention deficit hyperactivity disorder - Fatih Gültekin; Eray Metin Güler; Sümeyye Akın (Acta Medica Alanya)
Attention deficit hyperactivity disorder (ADHD) is a childhood-onset disorder that affects 5% to 12% of children worldwide. Etiological factors, including nutrition, contribute to this disease, which is characterized by inattention, impulsivity and hyperactivity symptoms. Fats, which form an important part of the daily diet, can have effects on ADHD and its symptoms. In the literature, it is stated that omega-3 fatty acids are low in children with ADHD, and supplementation studies may be effective in improving symptoms. In addition, high omega-6/omega-3 fatty acids ratio in the diet and diets rich in saturated and trans fatty acids are associated with ADHD. In this review, the relationship between ADHD and dietary fatty acids was evaluated.